การนำเสนอกลยุทธ์การบริหารโรงเรียนขนาดเล็กเพื่อยกระดับคุณภาพการศึกษา - ทัศพร ปูมสีดา (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The purposes of this research were 1) to study the conceptual framework of small schools management for educational quality enhancement 2) to examine the current and desired states of small schools management for educational quality enhancement. The sample was comprised of 375 small primary schools under the office of the basic education commission. The respondents were school directors and teachers committee with total of 608 respondents (81.07%). The research instruments included questionnaires, and assessment of the conceptual framework optimum. Statistical applications in analyzing data analysis were frequency, mean (), percentage, standard deviation (S.D.) and prioritize the needs by using PNImodified The finding were: 1) the conceptual framework of small schools management for educational quality enhancement consisted of two components: 1.1) small schools management ; academic management, budgeting management, personnel management and general management, and 1.2) educational quality ; Learning achievement and desired characteristics 2) the overall current states of small schools management for educational quality enhancement were in high level (=3.82, S.D.= 0.80) while the overall desired states of small school management for educational quality enhancement were in highest level (= 4.69, S.D.=0.53). Moreover, the averages of the desirable state were higher than the average of current state in every dimension. Following analysis of school management, academic management showed the highest need (PNImodified= 0.239). When analyzed as relate to educational quality, the highest need is in the area of learning achievement (PNImodified= 0.214) 3) the small school management strategies for educational quality enhancement consist of four main strategies: 1) Accelerate the development of academic administration in teaching and learning management to enhance the quality of education. 2) Development of budgetary management for expanding cooperation networks to mobilize resources to enhance the quality of education. 3) Development of Personnel Management for enhancing the efficiency of personnel to enhance educational quality. 4) Optimize general administration: develop learning resources both inside and outside the school to enhance educational quality, with eight sub-strategies and thirty-four procedures.